The Role of Environmental Management in Enhancing Ecotourism Development in Bantimurung National Park - Sulistio, Sulistio; Anas, M; Ashari, Fadlan; Rivai, Suleman (Journal Development Manecos, 2024)
An investigation examines environmental management methodologies which enhance the growth of ecotourism at Bantimurung National Park in South Sulawesi Indonesia. The qualitative research method examines present management practices together with their impact on tourism as well as defines current challenges and potential opportunities for improvement. Interviews with important stakeholders from park management and government departments and ecotourism facilities and tourist parties combined with park observations and document examination structured the data collection. Numerous sustainable practices installed by the park get hindered by restricted resources along with minimal community engagement and weak policy collaboration. The research underscores the critical value of local unity in management decisions alongside new funding methods and technological approaches to solve the problems affecting a famous ecotourism attraction. The research reveals major opportunities for environmental management improvement at the park by developing better policy frameworks and enhancing participation from communities and implementing technological solutions. The research adds to the expanding literature on sustainable tourism by presenting guidelines that assist other protected areas dealing with conservation-tourism balance concerns.